GAYA HIDUP DAN MOTIVASI BERPRESTASI SEBAGAI PREDIKTOR TERHADAP PRESTASI AKADEMIK GURU - Sara Sahrazad (Sosio e-Kons, 2016)
Lifestyle and achievement motivation is very important in the advancement of one's academic achievement then this study aims to determine the effect of lifestyle and the simultaneous of an academic achievement teachers who became a master student of XYZ University Jakarta. The samples in this research is a master student  of XYZ University Jakartathe profession as a teacher has a population of 90 people.  This study uses a quantitative research approach by means of two questionnaires distributed to spread the lifestyle questionnaire and achievement motivation. While the students' academic achievement measured by IPK. Based on the results of multiple regression analysis obtained by the regression equation Y = 0264 + 0721 X1 X2. With R2 = 0778, Fhitung = 66.6944; at 0:00 significance level <0.05 indicating that simultaneous lifestyle and achievement motivation affects academic achievement.Key Word: Life Style, Achievement Motivation, Academic Achievement.